A SEMIOTIC ANALYSIS OF VISUAL SIGNS AND MEANINGS ON PRINCE ALI SOUNDTRACK MUSIC VIDEO FROM ALADDIN MOVIE 2019 - Anisa Latifah; Dewanto Dewanto; Ari Astutik (EL2J (English Language and Literature Journal), 2023)
This study describes the visual signs and their meanings in the Prince Ali music video by Will Smith. This research aims to find out what visual signs and their meanings in Prince Ali's music videos. In this case, visual signs and their meaning are very important for music video viewers, because in every appearance of actors, actresses, and settings have a certain meaning. In this study focused only on visual signs and their meanings. There are 5 visual signs in this study, including appearance, manner, activity, props and setting. This study used a qualitative descriptive method in analyzing the data. Dyer's theory is used in this study to analyze visual signs and their meanings. The results of this study found 25 visual signs in Prince Ali music video. Furthermore, all the result indicated that the visual sign and its meaning in the music video are in accordance with the theory proposed by Dyer's. All results from this study include all types of visual signs.